a)
sinx+2sinxcosx=0
⇔sinx(1+2cosx)=0⇔[sinx=01+2cosx=0
⇔[x=kπcosx=−12(∗)
(∗)⇔cosx=cos2π3⇒x=±2π3+kπ
Vậy phương trình có nghiệm [x=kπx=±2π3+kπ(k∈Z)
b)
cos5x+cos2xcos5x=0
⇔cos5x(1+cosx2x)=0⇔[cos5x=01+cos2x=0
⇒[x=π10+kπ5cos2x=−1(∗)
(∗)⇔cos2x=cosπ⇒x=±π2+k2π
Vậy phương trình có nghiệm [x=π10+kπ5x=±π2+k2π(k∈Z)
c)
cotx−cosx=1−sinx
Điều kiện: sinx≠0⇒x≠kπ(k∈Z)
Khi đó phương trình đã cho ⇔cosxsinx−cosx=1−sinx⇔cosx(1−sinx)sinx−(1−sinx)=0
⇔(1−sinx)(cotx−1)=0⇔[sinx=1cotx=1⇒[x=π2+k2πx=π4+kπ(k∈Z)
(thỏa mãn điều kiện)
Vậy phương trình có nghiệm [x=π2+k2πx=π4+kπ(k∈Z)
d)
1+sinxcos3x+sinx+cos3x=0
⇔(1+sinx)(1+cos3x)=0
⇔[sinx=−1cos3x=−1⇔[x=−π2+k2πx=±π3+k2π3
Vậy phương trình có nghiệm [x=−π2+k2πx=±π3+k2π3(k∈Z)